Time-dependent spectrum analysis of high power gyrotrons - Schlaich, Andreas (Karlsruher Forschungsberichte aus dem Institut für Hochleistungsimpuls- und Mikrowellentechnik, 2015)
In this work, a novel measurement system for the analysis of the gyrotron RF output spectrum was developed. It enables unprecedented time dependent measurements within a large bandwidth, dynamic range and unambiguous RF indication in the entire D-Band (110-170 GHz). Special attention was given to the investigation of parasitic RF oscillations, and the analysis of the interplay of thermal cavity expansion and ionization-based space charge neutralization at the start of long RF pulses.